Вплив на становлення і розвиток наукової і практичної агрономії Полтавщини наукових досліджень грунтів В.В. Докучаєвим - Писаренко, П.В.; Опара, М.М.; Яцун, Т.П.; Кавалір, Л.В.; Хоролець, Н.І.; Яцун, Ю.В. (Питання історії науки і техніки, 2008)
Идеи и непосредственная деятельность В.В. Докучаева в значительной мере определили становление и развитие научных исследований грунтов и других вопросов агрономии в Полтавской губернии в конце ХIХ – начале ХХ вв. Ideas and V.V. Dokuchayev's direct activity have appreciably defined becoming and development of scientific researches of the ground and other questions of agronomics in the Poltava province at the end of the XIX-th – the beginning of the XX-th centuries.